IMPLEMENTATION OF EDUCATION PLANNING IN IMPROVING EDUCATIONAL QUALITY THROUGH 2013 CURRICULUM BASIC SCHOOL - Ima Hariyanti Ningsih; Retno Winarni; Roemintoyo Roemintoyo (Universitas Sebelas Maret, 2018)
Planning is the element and function of management the first and main among other management functions, so that in the field of education becomes the key implementation of educational activities to achieve educational goals for each type and a certain level of education. The purpose of this research is to know the implementation of education planning in SDN 02 Jetis. This research uses descriptive qualitative approach which has natural characteristic as direct data source. The data in this research is taken from observation, interview, and documentation. Research findings are vision planning, mission and school objectives, quality improvement through training of educators and learners. Apply the 2013 curriculum well to cultivate a social, insightful and creative attitude towards learners. See from the growing competence of teachers, the ability of students learn both from the academic and non-academic side showed improvement, and relationships with related institutions, parents learners more closely.